Enzymatic antagonism of Trichoderma spp., on hytophthora parasitica and Fusarium oxysporum in jamaica (Hibiscus sabdariffa L.) (Bioagro, 2021)
Mexico is the seventh largest producer in Jamaica and Guerrero agglomerates more than 70% of the national production. The crop presents important phytosanitary limitations, highlights the "black leg" associated with a complex of pathogens (Phytophthora parasitica and Fusarium oxysporum). Losses up to 100% are reported in areas without phytosanitary management. Due to the nature of the consumption of the final product, it is necessary to implement ecological strategies to manage the disease. The objective of the study was to quantify the chitinases and glucanases activity of Trichoderma spp. Isolates, and to evaluate their inhibitory effect in vitro on Phytophthora parasitica and Fusarium oxysporum. Strains Ta10, Ta11, Ta6 and Ta9 of T. asperellum and Ti14 of T. Inhamatum from soils cultivated with hibiscus and high incidence of P. parasitica and F. oxysporum in Guerrero were evaluated. The levels of chitinases and glucanases produced in all Trichoderma spp. were significant (p£0,05), it could be observed that Ta9 from T. asperellum showed the highest specific chitinase activity, in the case of Ti14 glucanases from T. inhamatum it obtained the highest levels. All the filtrates from the different isolates of Trichoderma spp. generated a substantial inhibition of mycelial growth of Fusarium oxysporum and Phytophthora parasitica. Consistently Ta9 of Trichoderma asperellum obtained inhibition percentages greater than 90% in both tests. A significant correlation was detected between the enzymatic activity and the inhibition of the growth of the Trichoderma spp isolates. on pathogens.
Keywords: Antibiosis; enzymatic activity; Hibiscus sabdariffa; Trichoderma asperellum; Trichoderma inhamatum